KARAKTERISTIK PENGGUNAAN PELAKU PERJALANAN DALAM PEMILIHAN MODA TRANSPORTASI PEKERJA DI KOTA JAKARTA BARAT - Gidion P. Adirinekso (Jurnal Riset Manajemen dan Bisnis, 2017)
"> Modes of transport workers in the city even become part of the traffic’s problems that have persisted.This is related to the conditions of workers in the city and availability of public transportation relatedto the place where they are live. Many studies in Indonesia about factors of the mode of transportworkers has been done by Lestari (2009), Ludfi Djakfar et all (2010), Widiarta (2010), Sijabar &Ratnasari (2013), Rahmawati (2014), Oktavia and Pandia (2013). Their studies conducting usingbinary logistic regression, but in this study, we try to use multinomial logistic regression. The motivesare expanding the scope of research, and also to capture the actual condition for labor in the city.This study conducted in West Jakarta district, as a growing city and become a second CBD in DKI.The aim of this study to show the factors which affect the urban worker who lives in West Jakartachooses their mode of transportation. This research found several factors like gender, married status,age, car ownership and motorcycle ownership affect labor to choose their mode of transportation.The policy implication regarding the result is how to improve the quality and quantity of publictransportations.Keywords: urban worker, mode of transportation, multinomial logistic regression